NEW NORMAL DAN PRAKTIK KEBUDAYAAN DI KOTA TERNATE - Nurfani .; Rudi S Tawary (Universitas Khairun, 2021)
AbstractThis article studies the impact of COVID-19 and the cultural adaptation process of the people of Ternate City. The practice of people's lives must adapt to this pandemic because people must have strategy to survive. Using qualitative research methods with a descriptive approach, this study describes that the impact of COVID-19 on Ternate culture is very diverse. These cultures are affected because people of Ternate as a cultural entity must adapt to a new environment that requires people to keep distance and maintain cleanliness. Starting from changes in Eid habits to washing hands are the impacts of COVID-19. On the other hand, the new normal policy which is an adaptation strategy for the corona virus has also not given good hope to Ternate's cultural life.Keywords: COVID-19, Adaptation, Ternate Culture